Foreword: Weaving what together? - Rolston, Holmes, 1932-2025, author; Cascade Books, publisher (Colorado State University. Libraries, 2019)
What is mainly woven together is Christian concern for Earth and for the poor on Earth, environmental ethics and environmental justice. That involves weaving together the theoretical and the practical, the rich and the poor, the past, present, and future, human uniqueness and humans fitted into the ecosystems they inhabit, how we are "distinctive" and "simultaneously wound up," integrated into everything else. This is a pivotal book at a hinge point in Earth history.
Weaving what together? - foreword
Keywords: Mastaler, James; environmental justice; Christian faith; past, present, and future